Synthesis of Biomaterial Hydroxyapatite from Limestone by Using Two-Step Conversion - Saiful Arif (Universitas Trunojoyo Madura, 2020)
Hydroxyapatite [Ca10(PO4)6(OH)2] is natural ceramic material which is often used for artificial bone reconstruction. In this research, hydroxyapatite was synthesized from mineral of Calcite (CaCO3) which obtained from the Campurdarat, Tulungagung. The hydroxyapatite synthesis steps are encompassed by the preparation of precursors and the synthesis process by using wet chemical manipulation or routes. The XRF characterization shows that the percentage of calcium from the raw material is around 99%. This study succesfully obtains the compound of Ca(OH)2as a source of hydroxyapatite. The concentration of H3PO4 in hydroxyapatite synthesis process influences the synthesis results. For the concentration of H3PO4 0.6 M is still found the compound of Ca(OH)2. The difference result is shown H3PO4 with concentration 0.8 M which the total synthesis product is hydroxyapatite.